Efficacy of antenatal corticosteroids in preterm twins: the EPIPAGE‐2 cohort study. (14th December 2017) - Palas, D; Ehlinger, V; Alberge, C; Truffert, P; Kayem, G; Goffinet, F; Ancel, P‐Y; Arnaud, C; Vayssière, C
Abstract : Objectives: To investigate the efficacy of antenatal corticosteroid (ACS) therapy on short‐term neonatal outcomes in preterm twins, and further document the influence of the ACS‐to‐delivery interval. Design: EPIPAGE‐2 is a nationwide observational multicentre prospective cohort study of neonates born between 22 and 34 completed weeks of gestation. Setting: All French maternity units, except in a single administrative region, between March and December 2011. Population: A total of 750 twin neonates born between 24 and 31 weeks of gestation. Methods: Exposure to ACSs was examined in four groups: single complete course, with an ACS administration‐to‐delivery interval of ≤7 days; single complete course, with an ACS‐to‐delivery interval of >7 days; repeated courses; or no ACS treatment. Main outcome measures: Neonatal outcomes analysed were severe bronchopulmonary dysplasia, periventricular leukomalacia or intraventricular haemorrhage grade III/IV, in‐hospital mortality, and a composite indicator of severe outcomes. Results: Compared with no ACSs, in multivariable analysis, a single course of ACSs with an administration‐to‐delivery interval of ≤7 days was significantly associated with a reduced rate of periventricular leukomalacia or intraventricular haemorrhage grade III/IV (aOR 0.2; CI 95% 0.1–0.5), in‐hospital mortality (0.3; 0.1–0.6), and the composite indicator (0.1; 0.1–0.3), whereas a single course of ACDs with an administration‐to‐delivery interval of >7 days did not significantly reduce the frequency of in‐hospital mortality (0.7; 0.3–1.8). No significant differences in terms of benefit or risk were found when comparing repeated courses with a single complete course. Conclusion: In preterm twins, a single complete course of antenatal corticosteroids was associated with an improvement of severe neurological outcome, whereas reduced in‐hospital mortality was seen only when the ACS‐to‐delivery interval was ≤7 days. Tweetable abstract: A single complete course of antenatal steroids reduced severe neurological morbidity in preterm twins (24–31 weeks). Tweetable abstract: A single complete course of antenatal steroids reduced severe neurological morbidity in preterm twins (24–31 weeks). This paper includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights15014